Foundations of physical activity and public health - Kohl, Harold W. III. 1960-; Murray, Tinker Dan 1951- (Human Kinetics, 2012)
This is a textbook which clearly defines the intersection of exercise science and public health. It offers a solid introduction to the concepts of public health and exercise science, the techniques used to measure physical activity and the health effects of exercise and physical activity.